Formycin B-resistant mutants of Chinese hamster ovary cells: novel genetic and biochemical phenotype affecting adenosine kinase. - Mehta, K D (1983)
Stable mutants which are approximately three- and eightfold resistant to the pyrazolopyrimidine nucleosides formycin A and formycin B (FomR) have been selected in a single step from mutagenized Chinese hamster ovary cells. In cell extracts, the two FomR mutants which were examined were both found to contain no measurable activity of the enzyme adenosine kinase (AK). However, cross-resistance studies with other adenosine analogs such as toyocamycin and tubercidin show that these mutants are distinct from toyocamycin or tubercidin resistant (Toyr) mutants which also contain no measurable AK activity in cell extracts. Studies on the uptake and incorporation of [3H]adenosine and [3H]tubercidin by various mutants and parental cell lines show that unlike the Toyr mutants, which are severely deficient in the phosphorylation of these compounds, the FomR mutants possess nearly normal capacity to phosphorylate these compounds and incorporate them into cellular macromolecules. These results suggest that the FomR mutants contain normal levels of AK activity in vivo. In cell hybrids formed between FomR X FomS cells and FomR X Toyr cells, the formycin-resistant phenotype of both of the FomR mutants behaved codominantly. However, the extracts from these hybrid cells contained either congruent to 50% (FomR X FomS) or no measurable (FomR X Toyr) AK activity, indicating that the lesion in these mutants neither suppresses the wild-type AK activity nor complements the AK deficiency of the Toyr mutants. The presence of AK activity in the FomR mutants in vivo, but not in their cell extracts, along with the codominant behavior of the mutants in hybrids, indicates that the lesions in the FomR mutant are of a novel nature. It is suggested that the genetic lesion in these mutants affects AK activity indirectly and that it may involve an essential cellular function which exists in a complex form with AK. Some implications of these results regarding the mechanism of action of formycin B are discussed.